Call to environmental legislation concerning the municipal solid waste in three municipalities of Minas Gerais - Rocha, Guilherme Henrique Rodrigues; Silva, Sabrina Soares da; Silva, Geiziana das Dores Nunes da; Duarte, Gabriela Rezende (Revista de Administração da UFSM, 2016)
It was analyzed three municipalities of Minas Gerais state, Pedra do Indaiá, Santo Antônio do Monte e Divinópolis, considering the fulfillment of the State and Federal legal requirements of Municipal Solid Waste (MSW), identifying limitations and potentialities of administrations. It was used information from the State Sanitation Information System (SSIS) and the National Sanitation Information System (NSIS), on-site observation and informal interviews with various actors of collection, transportation and disposal of MSW. It was found that the major constraints of the municipalities are financially driven and technical-administrative and none of the municipalities has, today, the ability to meet the legal requirements in their entirety. Currently, already occurs, adherence to public consortia that are presented as an effective alternative in compliance with legal requirements. Among the external factors it is considered as a major limitation the lack of awareness of the society and govern. So it is necessary a deeper approach to similar situations for the reformulation of practices that lead municipalities to compliance with the laws and thus provide better quality of life for citizens, through the social and environmental balance.